Gender Identity Lexicon as An Object of Translation - Nargiza Abdullayeva (Penerbit Jurnal Indonesia, 2024)
Gender lexical units occupy a special place in modern linguistics. There should also be specific approach to enriching the language of the work of art, giving the image of heroes, in the translation of the gender marked lexicon used by the authors. Words and phrases in the original text, which are common in male and female speeches, are also included. This article mainly describes gender identity lexicon as well as the differentiation of gendered expressive lexical units by researchers. In addition, in the translation of works of art, some thoughts are expressed on the issue of gender-component lexicon.